Developing of health literacy instrument on human kidney for senior high school student - Rindi Wahyuni; Agung Wijaya Subiantoro (Research and Development in Education (RaDEn), 2024)
Health literacy plays a pivotal role in shaping an individual's adoption of a healthy lifestyle, particularly among students transitioning into adolescence and adulthood. Hence, integrating health literacy into educational curricula is imperative. For instance, the study of the human kidney excretory system, which necessitates the use of measuring instruments, can serve as a platform to enhance students' health literacy skills within the realm of biology education. This study was conducted to develop and determine the feasibility of human kidney health literacy instruments. The research method used in this study is ADDIE development research which consists of 5 stages, including (1) preliminary needs analysis (2) product design (3) Development (4) Implementation, and (5) evaluation. The trial results stated that the instrument was feasible to use with a linguist assessment of 9.8% very feasible category, and a material expert of 91% very feasible category. The empirical validity test was conducted with a limited trial to 47 students of Al-Azhar 9 Yogyakarta High School and the results showed that 92% of the items were declared valid with a high reliability value of 0.7. This study produced 16 statement items on the attitude aspect, 6 items on the knowledge aspect, and items on the skill aspect. The total question items produced in this study were 24 question items that were valid and feasible to use as a tool to improve the quality of education.